2013
DOI: 10.1016/j.pt.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The invasive mosquito species Aedes albopictus: current knowledge and future perspectives

Abstract: One of the most dynamic events in public health is being mediated by the global spread of the invasive mosquito Aedes albopictus. Its rapid expansion and vectorial capacity for various arboviruses affect an increasingly larger proportion of the world population. Responses to the challenges of controlling this vector are expected to be enhanced by an increased knowledge of its biology, ecology, and vector competence. Details of population genetics and structure will allow following, and possibly predicting, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
476
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(493 citation statements)
references
References 83 publications
(139 reference statements)
6
476
0
11
Order By: Relevance
“…The high sequence identity of the virus that was detected in Aedes albopictus mosquitoes to those isolated in Japan would corroborate the hypothesis that these two viruses are the same or closely related (Roiz et al, 2012), but the analysis of the complete genome of these strains would be necessary to confirm this. It is thought that Aedes albopictus has most likely brought AeFV during its recent expansion from Japan to North America and Europe (Hawley et al, 1987;Rai, 1991;Benedict et al, 2007;Enserink, 2008;Bonizzoni et al, 2013). It has also been suggested that the nucleotide sequence is relatively well conserved because ISFs are not harmful to the mosquito host and because NS5 is not affected by host immunity (Obara-Nagoya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The high sequence identity of the virus that was detected in Aedes albopictus mosquitoes to those isolated in Japan would corroborate the hypothesis that these two viruses are the same or closely related (Roiz et al, 2012), but the analysis of the complete genome of these strains would be necessary to confirm this. It is thought that Aedes albopictus has most likely brought AeFV during its recent expansion from Japan to North America and Europe (Hawley et al, 1987;Rai, 1991;Benedict et al, 2007;Enserink, 2008;Bonizzoni et al, 2013). It has also been suggested that the nucleotide sequence is relatively well conserved because ISFs are not harmful to the mosquito host and because NS5 is not affected by host immunity (Obara-Nagoya et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the Asian tiger mosquito, A. albopictus (Skuse), deserves a standing-alone focus. Indeed, this is currently the most invasive mosquito worldwide (Benedict et al 2007), and its medical and veterinary importance is magnified by its daytime human-biting behaviour and the ability to vector, besides dengue, a wide number of other viruses, including La Crosse encephalitis, West Nile and chikungunya (Bonizzoni et al 2013). In addition, the possibility that the Zika virus may adapt to exploit A. albopictus as a vector is a noteworthy concern, since it has been previously highlighted that other arboviruses transmitted by Culicidae have adapted to domestic animals, including The malaria vaccine RTS,S/AS01 (RTS,S)] has been developed to fight P. falciparum, while it does not offer protection against P. vivax, which predominates in many countries outside of Africa.…”
Section: Eco-friendly Control Of Malaria and Arbovirus Vectors: A Crumentioning
confidence: 99%
“…Aedes spp. ), and has facilitated the transmission of tropical and subtropical pathogens to temperate regions (Paupy et al 2009, Bonizzoni et al 2013. There, alien species may also benefit from climate change (Takumi et al 2009, Walther et al 2009, Caminade et al 2012, Dobson et al 2013, causing additional pressure on human health (Keller et al 2011, Strayer 2012.…”
Section: Introductionmentioning
confidence: 99%